Morphometric and functional analysis of bovine oocytes obtained from abattoir ovaries and by transvaginal follicle aspiration in creole cows of the Ecuadorian Andean highland - Alvarado U., Jhonatan (2020)
This study assessed the morphometric and functional characteristics of oocytes from 10 native cows to the Ecuadorian Andes, collected by transvaginal follicular aspiration (OPU) and oocytes collected post mortem (PM) from abattoir ovaries. For this purpose, 1157 cumulus-oocyte complexes (CCOs) of the OPU group (n=271) and PM group (n=886) were recovered in 10 repetitions per group by follicular aspiration at 90 mm Hg pressure and classified as A, B or C, according to the characteristics of the cytoplasm and cumulus cells. The activity of the enzyme glucose 6 phosphate dehydrogenase (G6PD) was determined as an indicator of follicular growth and maturation and the integrity of the plasma membrane by staining the CCOs with cresyl brilliant blue (BCB +) and trypan blue, respectively. The size (diameter and volume) of the oocytes was evaluated using CaptaVisio® software v. 5.1. The data were analysed by logistic regression and by the SAS general linear model, and the means were compared by the least square method. The results showed that the oocytes of the PM group had a larger diameter (126.0 ± 0.48 vs. 122.7 ± 0.79 µm; p<0.01) and integrity of the plasma membrane (86.0 vs. 76.8%; p<0.05) than the OPU group. However, quality A and B oocytes did not show significant differences between groups with respect to plasma membrane integrity and BCB + values. The results suggest that, although the fact that the size and viability were more affected in the oocytes aspirated by OPU, those of quality A and B from both sources showed similar values regarding the integrity of the plasma membrane and metabolic condition to continue. maturation.